Neurônios Nadph diaforase positivo no córtex cerebral da lagartixa Podarcis hispânica - Pimentel, Hugo de Carvalho (2009)
The nitric oxide (NO) constitutes one of the most important mediators of the processes intra and extracellular. Amongst its biological functions, there is a role of neuromodulador. In Podarcis hispanica, diverse research had described the citoarchitecture of the cerebral cortex of this animal, however, there isn't data published about neurons that producers neuronal nitric oxide synthetase (nNOS). The aim of this work was to identify the positive NADPHd/nNOS neurons in the cerebral cortex of P. hispanica. For such, it was used the histochemistry technique NADPHd and imunochemistry to nNOS and soluble Guanylyl Cyclase (sGC α1). The results showed that the cerebral cortex of P. hispanica has a population of 1897 diaphorase positive neurons, being, 1090 (57,5%) in young animals, 528 (27,8%) in adults and 279 (14,7%) in age. Among the telencephalics levels, pre-comisural, comisural and post-comisural showed 423 (22,3%); 459 (24,2%) and 1015 (53,5%) neurons, respectively. In relation the cortical areas, the medial cortex (CM), dorsomedial (CDM), dorsal (CD) and lateral (CL) showed 86 (4,5%), 530 (27,9%), 1243 (65,5%) and 38 (2%) neurons, respectively. Inner and outer plexiforme layers showed, respectively, 1264 (66,6%), 533 (28,1%) and 100 (5.3%) neurons. 1737 (91,5%) NADPHd positive neurons had been found in the regions Timm-positive and 160 (8,5%) in the Timm-negative. 15 types of morphological NOS positive neurons were identified: piramidal, bouquet double, deep stellate, sarmentous, polymorphous, ectopic vertical multipolar, coral, granular unipolar, large radial, horizontal bipolar, horizontal unipolar, smooth vertical, spheroidal and fusiforme. In conclusion, the cerebral cortex of Podarcis hispanica showed neurons with NADPHd activity, as well as immunoreactive to the anti-nNOS and sGC α1 antibodies; NADPHd positive neurons are of three types: Type I, II and III; There is a significant difference in the number of NADPHd positive neurons among animals of different ages and among the cortical areas and layers and were found mainly in the Timm-positive regions.